Hollow Mesoporous Molybdenum Single-Atom Nanozyme-Based Reactor for Enhanced Cascade Catalytic Antibacterial Therapy - Zhang Z; Yang T; Wang J; Yu Z; Qiao Y; Wang C; Yue Z; Wu H (International Journal of Nanomedicine, 2023)
Zhijun Zhang,1,2 Tiehong Yang,2 Jingwei Wang,2 Zhe Yu,2 Youbei Qiao,2 Chaoli Wang,2 Zhenggang Yue,1 Hong Wu2 1School of Pharmacy, Shaanxi University of Chinese Medicine, Xi’an, People’s Republic of China; 2Department of Medicine Chemistry and Pharmaceutical Analysis, School of Pharmacy, Air Force Medical University, Xi’an, People’s Republic of ChinaCorrespondence: Hong Wu, Department of Medicine Chemistry and Pharmaceutical Analysis, School of Pharmacy, Air Force Medical University, Xi’an, People’s Republic of China, Tel/Fax +86 29 84776823, Email wuhong@fmmu.edu.cn Zhenggang Yue, School of Pharmacy, Shaanxi University of Chinese Medicine, Xi’an, People’s Republic of China, Tel +86 18092086211, Email liuxingjian1981@163.comPurpose: The remarkable peroxidase-like activity of single-atom nanozymes (SAzymes) allows them to catalyze the conversion of H2O2 to •OH, rendering them highly promising for antibacterial applications. However, their practical in vivo application is hindered by the near-neutral pH and insufficient H2O2 levels present in physiological systems. This study was aimed at developing a SAzyme-based nanoreactor and investigating its in vivo antibacterial activity.Methods: We developed a hollow mesoporous molybdenum single-atom nanozyme (HMMo-SAzyme) using a controlled chemical etching approach and pyrolysis strategy. The HMMo-SAzyme not only exhibited excellent catalytic activity but also served as an effective nanocarrier. By loading glucose oxidase (GOx) with HMMo-SAzyme and encapsulating it with hyaluronic acid (HA), a nanoreactor (HMMo/GOx@HA) was constructed as glucose-triggered cascade catalyst for combating bacterial infection in vivo.Results: Hyaluronidase (HAase) at the site of infection degraded HA, allowing GOx to convert glucose into gluconic acid and H2O2. An acid environment significantly enhanced the catalytic activity of HMMo-SAzyme to promote the further catalytic conversion of H2O2 to •OH for bacterial elimination. In vitro and in vivo experiments demonstrated that the nanoreactor had excellent antibacterial activity and negligible biological toxicity.Conclusion: This study represents a significant advancement in developing a cascade catalytic system with high efficiency based on hollow mesoporous SAzyme, promising the advancement of biological applications of SAzyme. Keywords: nanozyme, nanocarrier, glucose oxidase, reactive oxygen species, bacterial infection